High-Throughput Selection, Enumeration, Electrokinetic Manipulation, and Molecular Profiling of Low-Abundance Circulating Tumor Cells Using a Microfluidic System - Dharmasiri, Udara (Anal Chem, 2011)
[Image: see text] A circulating tumor cell (CTC) selection microfluidic device was integrated to an electrokinetic enrichment device for preconcentrating CTCs directly from whole blood to allow for the detection of mutations contained within the genomic DNA of the CTCs. Molecular profiling of CTCs can provide important clinical information that cannot be garnered simply by enumerating the selected CTCs. We evaluated our approach using SW620 and HT29 cells (colorectal cancer cell lines) seeded into whole blood as a model system. Because SW620 and HT29 cells overexpress the integral membrane protein EpCAM, they could be immunospecifically selected using a microfluidic device containing anti-EpCAM antibodies immobilized to the walls of a selection bed. The microfluidic device was operated at an optimized flow rate of 2 mm s(−1), which allowed for the ability to process 1 mL of whole blood in <40 min. The selected CTCs were then enzymatically released from the antibody selection surface and hydrodynamically transported through a pair of Pt electrodes for conductivity-based enumeration. The efficiency of CTC selection was found to be 96% ± 4%. Following enumeration, the CTCs were hydrodynamically transported at a flow rate of 1 μL min(−1) to an on-chip electromanipulation unit, where they were electrophoretically withdrawn from the bulk hydrodynamic flow and directed into a receiving reservoir. Using an electric field of 100 V cm(−1), the negatively charged CTCs were enriched into an anodic receiving reservoir to a final volume of 2 μL, providing an enrichment factor of 500. The collected CTCs could then be searched for point mutations using a PCR/LDR/capillary electrophoresis assay. The DNA extracted from the CTCs was subjected to a primary polymerase chain reaction (PCR) with the amplicons used for a ligase detection reaction (LDR) to probe for KRAS oncogenic point mutations. Point mutations in codon 12 of the KRAS gene were successfully detected in the SW620 CTCs for samples containing <10 CTCs in 1 mL of whole blood. However, the HT29 cells did not contain these mutations, consistent with their known genotype.